Is foreign aid concentrated increasingly on needy and deserving recipient countries? An analysis of Theil indices, 1995-2015 - Frank Bickenbach; Asithandile Mbelu; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2017)
By tracking the changes in different margins of Theil indices during the period 1995-2015, we re-consider the question of whether bilateral and multilateral donors have targeted aid increasingly to particularly needy recipient countries with relatively good governance in order to improve the effectiveness of aid. According to our findings, the Paris Declaration on Aid Effectiveness in 2005 has not changed the donors' aid allocation systematically and consistently. Bilateral aid has become slightly more concentrated on poorer recipient countries, but most donors became less selective in granting aid to higher income countries. Furthermore, the Paris Declaration did not help improve the merit-based allocation of aid. Finally, there is no compelling evidence suggesting that donors have become less self-interested in using aid as a means to promote their own exports.
Keywords: F23; 330; foreign aid; Theil index; bilateral donors; multilateral donors; recipient need; recipient merit